PENERAPAN INTEGRASI ALKITAB: STUDI KASUS DI UNIVERSITAS PELITA HARAPAN - Daniel Winardi (STT Bethel The Way, 2020)
The application of Biblical integration is the core of Christian education. Universitas Pelita Harapan is one of many universities that has a Conservatory of Music, in the Faculty of Art, and commits to implement Christian education in its learning process. This study was conducted in January-April 2016 to know: 1) How Biblical integration is designed in Faculty’s core curriculum; 2) In what level Biblical integration is applied in Faculty lectures nowadays; 3) What are the challenges and obstacles faced by the lecturers while/want to apply Biblical Integration. With qualitative approach, data was collected by using interview, questionairre, documents, and observation. The subjects of this study were 1 Vice Rector, 1 Dean, 1 Head Study, 10 full time lecturers, and 40 students. The research shows that: 1) Biblical integration has not been designed in Faculty curriculum, especially in SAP; 2) The application of Biblical integration has not been done comprehensively; 3) Not only lecturers experience some difficulties to integrate the subject with the Bible in SAP, but also not all students in the Faculty are Christians.